Proceedings of the 12th International Conference on Advances in Mobile Computing and Multimedia 2014
DOI: 10.1145/2684103.2684112
|View full text |Cite
|
Sign up to set email alerts
|

A Model-based Approach for Engineering Multimodal Mobile Interactions

Abstract: Mobile phones have benefited from many enhancements since several years, including an increasing number of their embedded sensors (accelerometer, light sensor...). Created for giving contextaware abilities, these sensors also allow new types of interaction and pave the way to a great expansion of multimodal mobile interactions. Unfortunately, the current context of mobile software development makes difficult the development of multimodal applications. We propose our model-based solution that aims to facilitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
(25 reference statements)
0
0
0
1
Order By: Relevance
“…MIMIC (MobIle MultImodality Creator) [14] est un Framework à base de modèles pour la construction d'applications mobiles multimodales. Il permet la modélisation graphique des interactions multimodales en entrée et en sortie avec un langage de modélisation appelé M4L (Mobile MultiModality Modeling Language) ainsi que la génération automatique du code de ces interactions (sous Android, iOS et HTML5/CSS3) [13].…”
Section: éTat De L'artunclassified
“…MIMIC (MobIle MultImodality Creator) [14] est un Framework à base de modèles pour la construction d'applications mobiles multimodales. Il permet la modélisation graphique des interactions multimodales en entrée et en sortie avec un langage de modélisation appelé M4L (Mobile MultiModality Modeling Language) ainsi que la génération automatique du code de ces interactions (sous Android, iOS et HTML5/CSS3) [13].…”
Section: éTat De L'artunclassified
“…Elouali et al [14] suggested benefiting from this mobile technology for multimodal interaction. More specifically, smartphones are nowadays equipped with multiple sensors (gyroscope, compass, microphone, camera…) which can be used to acquire a large spectrum of user input and utilizing a various interaction modalities.…”
Section: Introductionmentioning
confidence: 99%